Strategi Manajemen Pemasaran PT. Indonesia Kamera Group - Febri Fidyantaka; Edy Sulistiyawan; Wira Yudha Alam (Yayasan Literasi Sains Indonesia, 2025)
In the rapidly evolving digital era, the photography and videography industry has undergone major changes, both in terms of technology and the way companies operate. PT Indonesia Kamera Group (Indonesia Kamera) is one of the companies that actively adapts to these changes. They offer services such as buying and selling, rental, and repair of photo and video equipment, photography and videography services, as well as providing freelance crews. Indonesia Kamera also forms partnerships to expand its reach and improve service quality. As a key player in the industry, Indonesia Kamera serves both individual and business needs. However, technological advancements and shifts in consumer behavior demand that the company enhance its competitiveness both online and offline. The online market offers great opportunities to expand reach, while the offline market remains important as many customers still prefer direct interaction and personalized service. Therefore, it’s essential for Indonesia Kamera to strengthen its marketing and operational strategies. This research aims to explore management strategies that can increase their value proposition. The focus includes digital marketing, customer service, operational efficiency, and business partnerships. The findings of this research are expected to help Indonesia Kamera grow and maintain its position amid the increasingly competitive industry landscape.